الإرسالية التبشيرية الأمريكية ورواد النهضة الفكرية العربية في بلاد الشام خلال القرن 19 م - فرحات, الكاملة (جامعة الوادي - University of Eloued, 2019)
The Christian missions in the Levant are considered as one of the most important western penetration means inside the Ottoman Empire during 19th century, in order to expedite the division of its legacy under the name of the sick man; here in our article we focus on the American missionaries which started realizing their aims through education, translation and publishing books using Arabic language as a bridge , and standing on educated personalities like : El- CHIDIAC , ElYAZIGI, who were appeared in the field of knowledge . This interchange leads to the development of intellectual life and the increase of conscience level by dint of the journalism and the movement of authoring, what is worth mentioning is that enlightenment which had spread in Levant, expanded to the neighboring countries and Egypt .
مقال
Keywords: Missionaries -Christian missions – translation – enlightenment-authoring-intellectual renaissance